2020
DOI: 10.1002/mp.14805
|View full text |Cite
|
Sign up to set email alerts
|

FAIR‐compliant clinical, radiomics and DICOM metadata of RIDER, interobserver, Lung1 and head‐Neck1 TCIA collections

Abstract: Published in Medical Physics, Vol. 47, No. 11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some of the aforementioned issues can be ameliorated by following FAIR data principles. Kalendralis et al [14] have shown how semantic ontologies can be used to apply syntactic standards to, and provide descriptive metadata about feature extraction methods on top of, existing medical data but without editing the original source data itself. Semantic Web standards based on the resource descriptor framework (RDF) can be used to store data with persistent unique identifiers, in such a way that is completely agnostic to the underlying database schema in the original data source [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the aforementioned issues can be ameliorated by following FAIR data principles. Kalendralis et al [14] have shown how semantic ontologies can be used to apply syntactic standards to, and provide descriptive metadata about feature extraction methods on top of, existing medical data but without editing the original source data itself. Semantic Web standards based on the resource descriptor framework (RDF) can be used to store data with persistent unique identifiers, in such a way that is completely agnostic to the underlying database schema in the original data source [15].…”
Section: Introductionmentioning
confidence: 99%
“…Above and beyond the FAIR principles, scientific collaboration can be encouraged at the health systems and institutions level by homogenizing data collection in clinical routine procedures and allowing multi-institutional sharing of data [14].…”
Section: Introductionmentioning
confidence: 99%
“…In “FAIR‐compliant clinical, radiomics and DICOM metadata of RIDER, Interobserver, Lung1 and Head‐Neck1 TCIA collections” by Kalendralis et al 10 describe updated clinical data, radiomics features, and Digital Imaging and Communications in Medicine (DICOM) headers from four datasets analyzed as part of their Nature Communications radiomics study 11 in order to support repeatability, reproducibility, generalizability, and transparency in radiomics research, which can be used as useful benchmark for future CT radiomics studies.…”
Section: Introductionmentioning
confidence: 99%